Daytime sleepiness in adolescents using smartphone - Sülün, Ayşe; Günay, Ulviye; Sarman, Abdullah; Dertli, Semiha (Journal of Dependence, 2020)
Objective: The aim of this study is to examine the relationship between daytime sleepiness in adolescents and smartphone usage dependence in adolescents in Turkey. Method: This study is a descriptive research. The sample consisted of 467 adolescents in three schools selected by simple random sampling method from the high school of Malatya Provincial Directorate of National Education. Sociodemographic data form, pediatric Daytime Sleepiness Scale and Smartphone Addiction Scale were used in the data collection. Results: Of the adolescents who participated in the study, 53.3% were within the 17-19 age range, 53.3% were male, and 30.8% were 12. it was determined that 52% had income of TL 2000 and above, 58.9% had 1-3 siblings, 54.8% were affected by school success due to smartphone use and 84% of them were affected. According to the correlation analysis, there was a moderate positive correlation between smartphone addiction and daytime sleepiness. Conclusion: Among adolescents who participated in the study, daytime sleepiness increased as the risk of phone addiction increased.